IDNLearn.com provides a user-friendly platform for finding and sharing accurate answers. Get step-by-step guidance for all your technical questions from our dedicated community members.

6y - 9x = 24
-3y + 2x=7



Sagot :

Answer:

(x, y) = (-38/5, -38/5)

Step-by-step explanation:

6y - 9x = 24

-3y + 2x = 7 $\Rightarrow$ -6y + 4x = 14.

Adding the two equtions together, we get:

(6y - 9x) + (-6y + 4x) = 24 + 14.

Simplifying, we get:

-9x + 4x = 38

-5x = 38

x = -38/5.

So, 6y - 9 * (-38/5) = 24

y = -37/5

Answer:

Step-by-step explanation:

6y - 9x = 24

-6y + 6x = 21

-3x = 45

x = -15

-3y - 30 = 7

-3y = 37

y = -37/3